A Comparative Approach of Cultural Intelligence Profile of Management and Non-Management Romanian Students - Laura BRANCU; Valentin MUNTEANU; Ionut GOLET (Revista de Management Comparat International)
This paper discusses the results of a comparative research related to cultural intelligence (CQ) carried out for a sample of Romanian students of the same university from various fields of study. Cultural intelligence (CQ) is defined as the as individuals’ ability to act efficiently in different cultural contexts. Due to a significant growth of Internet-based communication, enabling virtual work teams, geographically and culturally dispersed (Stanko & Gibson , 2009), and to increased globalization over the past 20 years, the number of people who currently get in touch with other cultures has grown significantly (Eisenberg et al., 2013). In this context, it could be consider that developing cross - cultural competencies is useful, even necessary, for professionals in all fields, not only for current or future managers. Consequently, in order to better understanding students' CQ, we classified them into two distinct groups, management and non-management students, using Earley & Ang’s (2003) multidimensional concept as an analysis framework. Because CQ is a multidimensional concept, this paper will discuss the answers for each of the four CQ dimensions, in order to identify which of the four capabilities is more or less developed among students and which are the significant similarities and differences between the two groups of students. Taking into account that literature highlights the influence of crosscultural management academic courses on CQ (Eisenberg et al. 2013, Putranto et al., 2015; Ramsey & Lorentz, 2016), our main purpose is to understand differences/similarities between the two groups and consequently, adapting the university curricula to students' real needs related to developing their CQ. This paper discusses the results of a comparative research related to cultural intelligence (CQ) carried out for a sample of Romanian students of the same university from various fields of study. Cultural intelligence (CQ) is defined as the as individuals’ ability to act efficiently in different cultural contexts. Due to a significant growth of Internet-based communication, enabling virtual work teams, geographically and culturally dispersed (Stanko & Gibson , 2009), and to increased globalization over the past 20 years, the number of people who currently get in touch with other cultures has grown significantly (Eisenberg et al., 2013). In this context, it could be consider that developing cross - cultural competencies is useful, even necessary, for professionals in all fields, not only for current or future managers. Consequently, in order to better understanding students' CQ, we classified them into two distinct groups, management and non-management students, using Earley & Ang’s (2003) multidimensional concept as an analysis framework. Because CQ is a multidimensional concept, this paper will discuss the answers for each of the four CQ dimensions, in order to identify which of the four capabilities is more or less developed among students and which are the significant similarities and differences between the two groups of students. Taking into account that literature highlights the influence of crosscultural management academic courses on CQ (Eisenberg et al. 2013, Putranto et al., 2015; Ramsey & Lorentz, 2016), our main purpose is to understand differences/similarities between the two groups and consequently, adapting the university curricula to students' real needs related to developing their CQ.